Aging and sleep deprivation affect different neurocognitive stages of spatial information processing during a virtual driving task – An ERP study - Rashid Izullah Faramosh; Koivisto Mika; Nieminen Valtteri; Luimula Mika; Hämäläinen Heikki (Elsevier Ltd, 2022)
We have previously shown that aging deteriorates detection of spatial visual and auditory stimuli and prolongs reaction times measured during a virtual driving task. Sleep deprivation affected the young more than the old. Here we determined the effects of age and sleep deprivation on ERPs elicited by spatial visual and auditory stimuli during virtual driving. Participants were 22 young (18–35 years) and 19 old (65–79) healthy males. Experiments were run in normal daytime condition and after a night of sleep deprivation. Aging shortened the peak latencies of the early P1 and N1 but increased the P3 latency. Sleep deprivation slowed down and diminished the N1 peaks of the young. General right-side preference was seen in latencies. Thus, the effects of aging could be seen in decision making and working memory related processes (P3), whereas those of sleep deprivation could be found in alerting and orienting functions (N1) in the young.